2018
DOI: 10.1002/dmrr.3004
|View full text |Cite
|
Sign up to set email alerts
|

Risk of dipeptidyl peptidase‐4 (DPP‐4) inhibitors on site‐specific cancer: A systematic review and meta‐analysis

Abstract: The long-term impact of dipeptidyl peptidase-4 (DPP-4) inhibition is unknown, and there are concerns about the influence of DPP-4 inhibition on carcinogenesis of the pancreas and thyroid. As DPP-4 is a rather unselective enzyme present in many tissues, we focused on all specific cancer types. PubMed and EMBASE were searched between January 2005 and April 2017 to identify studies comparing DPP-4 inhibitors with either placebo or active drugs on cancer risk. Studies were included if they reported on at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 53 publications
1
23
1
Order By: Relevance
“…The interest in the incident malignancy with DPP-4 inhibitor use received its attention when 223 cases of pancreatic cancer were reported from sitagliptin use in Food and Drug Administration Adverse Event Reporting System (FAERS) from 2007 to 2011 36. Nonetheless, a large number of studies including meta-analyses revealed no increased risk of site-specific malignancy with DPP-4 inhibitors 22,3740. In accordance with the previous results, this study also displayed the evidence of low risk for malignancy with DPP-4 inhibitors in T2DM patients.…”
Section: Discussionsupporting
confidence: 91%
“…The interest in the incident malignancy with DPP-4 inhibitor use received its attention when 223 cases of pancreatic cancer were reported from sitagliptin use in Food and Drug Administration Adverse Event Reporting System (FAERS) from 2007 to 2011 36. Nonetheless, a large number of studies including meta-analyses revealed no increased risk of site-specific malignancy with DPP-4 inhibitors 22,3740. In accordance with the previous results, this study also displayed the evidence of low risk for malignancy with DPP-4 inhibitors in T2DM patients.…”
Section: Discussionsupporting
confidence: 91%
“…Research about dipeptidyl peptidase-4 (DPP-4) inhibitors, which function via a similar mechanism as GLP-1 receptor agonists, failed to verify an association between the use of these drugs and an increased risk of site-specific cancer, and this was attributed to the small number of studies for each cancer type and their relatively short duration [50]. Another meta-analysis published in 2017 that included four large-scale studies indicated that GLP-1 receptor agonists did not increase the risk of pancreatic cancer [51], and our study further demonstrated that GLP-1 receptor agonist therapy was not associated with an increased risk of any of the malignant neoplasms studied.…”
Section: Discussionmentioning
confidence: 99%
“…However, later years did not confirm these findings. Meta-analysis of site-specific cancers associated with DPP-4 inhibitors use in 12 RCTs and 13 observational studies did not reveal elevated cancer risk in DPP-4 inhibitors' users [103]. The most recent meta-analysis of 157 RCTs, performed by Dicembrini and colleagues, revealed neutral effect of DPP-4 inhibitors on overall cancer risk, irrespective of molecule studied and cancer site, with the exception of colorectal cancer, in which DPP-4 inhibitors use was associated with its significantly reduced risk [104].…”
Section: Dipeptidil-peptidase-4 Inhibitorsmentioning
confidence: 86%
“…The associations between incretin-based therapies and cancer are still not fully elucidated. Although there are some concerns regarding DPP-4 inhibitors and breast cancer and its metastasis risk, it seems that both DPP-4 inhibitors and GLP-1 receptor agonists can be considered neutral, or even beneficial (decreased risk of colorectal cancer in case of DPP-4 inhibitors) [99][100][101][102][103][104][105][106][107][108]. Hopes associated with GLP-1 receptors agonists use in terms of cancer risk were not confirmed, despite their beneficial effect on glycemia, body weight, blood pressure, liver steatosis and insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%